Tidally driven topographic eddies exploited by manta feeding aggregations - Harvey Cairns; Daniel Conley; Christopher Stokes; Tim Scott; Phil Hosegood (Estuarine, Coastal and Shelf Science, 2026)

Early Imaging Biomarkers of Cartilage Strain After ACL Reconstruction Predict Patient Pain and Altered Knee Loading - Emily Y. Miller; Timothy Lowe; Hongtian Zhu; Woowon Lee; Pablo F. Argote; Danielle Dresdner; James Kelly; Rachel M. Frank; Eric McCarty; Jonathan Bravman; Daniel Stokes; Nancy C. Emery; et al. (Annals of Biomedical Engineering, 2026)
Purpose To investigate temporal evolution of cartilage strain and relaxometry following ACL reconstruction, and examine associations between MRI metrics, pain, and knee loading patterns during gait as potential early markers of cartilage degeneration. Methods Twenty-five participants (15 female, 10 male; mean age 25.6 years) undergoing ACL reconstruction completed MRI assessments at 6 and 12 month post-surgery, including displacement-encoding MRI (intratissue strain) and quantitative relaxometry (T2, T2*, T1ρ). Pain was evaluated using patient-reported outcome scores. Gait analysis quantified knee adduction moment, knee extension moment, and knee flexion moment at 12 months in a subset of patients. Correlations between MRI metrics in cartilage contact regions, patient-reported outcomes, and knee loading were evaluated. Results Between 6 and 12 month post-reconstruction, increased tibial compressive and transverse strains correlated with worsening pain, while increased tibial shear strain associated with reduced pain and improved outcomes. Participants demonstrating greater symptom improvement exhibited higher knee adduction moments, which associated with favorable compositional changes including decreased femoral T1ρ and decreased tibial hydrostatic strain. Higher knee extension moments associated with increased tibial compressive and hydrostatic strain. Conclusion Cartilage strain and T1ρ changes associate with pain and altered loading patterns, suggesting potential as early post-traumatic osteoarthritis markers. The observed links between knee loading patterns and cartilage structural changes highlight beneficial adaptation of the reconstructed knee to mechanical loading, and potential avenues for early therapeutic (gait-modifiable) intervention. Advanced MRI may enable early identification of at-risk patients following ACL reconstruction.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Techno-economic and carbon dioxide emission assessment of carbon black production - Fabian Rosner; Trisha Bhagde; Daniel S. Slaughter; Vassilia Zorba; Jennifer Stokes-Draut (Journal of Cleaner Production, 2024)

Satellite-based shoreline detection along high-energy macrotidal coasts and influence of beach state - Aikaterini Konstantinou; Tim Scott; Gerd Masselink; Kit Stokes; Daniel Conley; Bruno Castelle (Marine Geology, 2023)

Environmental drivers of earthworm communities along an elevational gradient in the French Alps - Quentin Gabriac; Pierre Ganault; Isabelle Barois; Eduardo Aranda-Delgado; Elisa Cimetière; Jérôme Cortet; Montan Gautier; Mickaël Hedde; Daniel F. Marchán; José Carlos Pimentel Reyes; Alexia Stokes; Thibaud Decaëns (European Journal of Soil Biology, 2023)

Borderless conservation: Integrating connectivity into high seas conservation efforts for the Salas y Gómez and Nazca ridges - Ben Boteler; Daniel Wagner; Carole Durussel; Emily Stokes; Carlos F. Gaymer; Alan M. Friedlander; Daniel C. Dunn; Felipe Paredes Vargas; David Veliz; Carolina Hazin (Frontiers in Marine Science, 2022)
Connectivity is essential to consider in area-based marine conservation measures because it greatly impacts vital ecological processes (e.g., recycling nutrients, regulating temperature, sequestering carbon, and supporting the life cycle of species). However, it is generally not well studied or integrated into conservation measures, particularly in the Southeast Pacific. This region is home to the Salas y Gómez and Nazca ridges, two adjacent seamount chains that stretch between the Peruvian coast and Rapa Nui (i.e., Easter Island). The area has been recognized for its exceptional natural and cultural significance as well as one of the most important global areas to protect. However, over 73% of the ridges are in areas beyond national jurisdiction, where they are unprotected and under threat. This study provides a synthesis of what we know about connectivity in the Salas y Gómez and Nazca ridges and provides practical recommendations for integrating this knowledge into conservation and management measures for the region. While data on connectivity is still limited, it should not constrain the development of conservation measures, which should be co-designed and co-developed, leveraging the expertise of international working groups throughout the region. Due to their high rates of endemism, as well as importance as migratory corridors, enacting large-scale conservation measures would address important conservation considerations for both connectivity and endemism. Enacting such large-scale conservation measures would not only elevate the Salas y Gómez and Nazca ridges as an exemplary case study, providing lessons for other marine regions seeking to implement similar measures, but could also help raise awareness on the severity of externally originating threats like climate change and plastic pollution to global audiences.

Rapid detection of carbapenemase-producing organisms directly from blood cultures positive for Gram-negative bacilli - William Stokes; Johann Pitout; Lorraine Campbell; Deirdre Church; Daniel Gregson (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Using RNA interference to determine the role of varisin in the innate immune system of the hard tick Dermacentor variabilis (Acari: Ixodidae) - Wayne L. Hynes; Martha M. Stokes; Shannon M. Hensley; S. Michelle Todd; Daniel E. Sonenshine (Experimental and Applied Acarology, 2008)

Social‐Psychological Principles of Community‐Based Conservation and Conservancy Motivation: Attaining Goals within an Autonomy‐Supportive Environment - DANIEL DeCARO; MICHAEL STOKES (Conservation Biology, 2008)
Community‐based natural resource conservation programs in developing nations face many implementation challenges underpinned by social‐psychological mechanisms. One challenge is garnering local support in an economically and socially sustainable fashion despite economic hardship and historical alienation from local resources. Unfortunately, conservationists' limited understanding of the social‐psychological mechanisms underlying participatory conservation impedes the search for appropriate solutions. We address this issue by revealing key underlying social‐psychological mechanisms of participatory conservation. Different administrative designs create social atmospheres that differentially affect endorsement of conservation goals. Certain forms of endorsement may be less effective motivators and less economically and socially sustainable than others. From a literature review we found that conservation initiatives endorsed primarily for nonautonomous instrumental reasons, such as to avoid economic fines or to secure economic rewards, are less motivating than those endorsed for autonomous reasons, such as for the opportunity for personal expression and growth. We suggest that successful participatory programs promote autonomous endorsement of conservation through an administrative framework of autonomy support—free and open democratic participation in management, substantive recognition and inclusion of local stakeholder identity, and respectful, noncoercive social interaction. This framework of the autonomy‐supportive environment (self‐determination theory) has important implications for future research into program design and incentive‐based conservation and identifies a testable social‐psychological theory of conservancy motivation.